Dental Scan and Mucormycosis: A Literature Review (Indian Journal of Contemporary Dentistry, 2022)
The purpose of this study was to describe common radiographic patterns that may be useful in predictingthe diagnosis of rhinocerebral mucormycosis. Methods: We retrospectively evaluated the imaging andclinical data of four males and one female, 3 to 72 years old, with rhinocerebral mucormycosis. Results:All the patients presented with sinusitis and ophthalmological symptoms. Most of the patients (80%)had isointense lesions relative to brain in T1-weighted images. The signal intensity in T2-weightedimages was more variable, with only one (20%) patient showing hyperintensity. A pattern of anatomicinvolvement affecting the nasal cavity, maxillary sinus, orbit, and ethmoid cells was consistentlyobserved in all five patients (100%). Our series demonstrated a mortality rate of 60%. Conclusion:Progressive and rapid involvement of the cavernous sinus, vascular structures and intracranial contentsis the usual evolution of rhinocerebral mucormycosis. In the context of immunosupression, a pattern ofnasal cavity, maxillary sinus, ethmoid cells, and orbit inflammatory lesions should prompt the diagnosisof mucormycosis. Multiplanar magnetic resonance imaging shows anatomic involvement, helping insurgery planning. However, the prognosis is grave despite radical surgery and antifungals.
Keywords: Rhinocerebral mucormycosis, imaging findings, MRI, neuroradiology